Evaluación técnica y financiera de la eficiencia del completamiento actual de un pozo del campo B en la cuenca Caguán Putumayo mediante un análisis nodal (2018)
The present thesis, has as main objective perform a technical and financial evaluation of the efficiency of the current completion of the well 4D in the field B, located on the Caguan-Putumayo Basin, by means of the software Prosper from Petroleum Experts emphasized on the nodal analysis given by the enterprise, gathering information of the: well files status, reservoir, production, production fluids and production facilities in surface, generating a data base for the well 4D which one will be proceed to perform the simulation. Afterwards, having the results of the actual completion simulation, it will be proposed 4 scenarios of workover jobs where each one considered a different artificial lift system: Elesctosumersible pumping, rod pumping, progressive cavity pumping, finally gas lift; where each one of them will be performed a simulation in order to evaluate technically the best. Finally, it was performed a financial analysis by means of the relation cost-benefit and the indicator net present value (NPV), based in the four scenarios proposed on the workover job, with the objective of evaluate which of these jobs will result financially in the more attractive for the production optimization of the enterprise.